IMPLEMENTASI WEBSITE VIRTUAL REALITY TOUR BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN LITERASI MATEMATIKA SISWA - Nur Hasanah; Eko Andy Purnomo; Venissa Dian Mawarsari (Jurnal Karya Pendidikan Matematika, 2024)
Mathematical literacy relates to how people apply knowledge in real-life situations. Based on the results of PISA from 2000 to 2018, the mathematical literacy of Indonesian students is still low. The use of inappropriate teaching media is one cause of this issue, thus there is a need for technology-integrated innovation to help improve mathematical literacy. The research is experimental with a one-group pretest-posttest design. The implementation is carried out systematically by administering a pretest, then treatment, followed by a posttest. The pretest results had an average of 41.44 and the posttest results were 75.49, indicating an increase in average test scores. The pre-analysis test indicates the research instruments are feasible to use, while the paired sample t-test results show 0.000 < 0.05, indicating the VR Tour website media with an ethnomathematics approach has a significant effect on mathematical literacy. Further data analysis from the n-gain test shows 0.30 < 0.5870 < 0.70, which has medium criteria, thus indicating an increase in mathematical literacy before and after the VR Tour website media with an ethnomathematics approach. The conclusion is that the VR Tour website media with an ethnomathematics approach is effective in improving mathematical literacy.